Dampak Hukum Penetapan Kawasan Pangan Nusantara Di Provinsi Sulawesi Tengah - Safrin, Mohamad; Syamsuddin, Adiesty S. P. (Jurnal Restorative Justice, 2024)
The Unitary State of the Republic of Indonesia is founded on the unity of the territory of the Provinceand Regency/City as regulated by Article 18 paragraph (1) of the 1945 Constitution of the Republic ofIndonesia. This article is the constitutional basis for forming Law Number 23 of 2014 concerningRegional Government, which accommodates regulations regarding the division of government affairs,including food affairs. This study aims to identify and describe the legal impact of the determination ofTalaga Village, Dampelas District, Donggala Regency, Central Sulawesi Province as the IndonesianFood Area, which was formed based on the Decree of the Governor of Central Sulawesi Number504/117.1/DBMPR-G.ST/2022 concerning the Determination of Talaga Village, Dampelas District,Donggala Regency, as the Indonesian Food Area for the National Food Provision Improvement Program(Food Estate). This research is normative legal research, using a statute and conceptual approach. Thelegal materials used are laws and regulations at the Central and Regional levels of Central SulawesiProvince and legal concepts taken from the latest legal references. The results of the study concludedthat there are several legal impacts of the determination of the Food Estate in Central Sulawesi Province, in environmental law, forestry law, spatial planning, and agrarian disputes aspects.